2011
DOI: 10.2147/copd.s23695
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IL-8 production from airway cells by tiotropium bromide in vitro

Abstract: BackgroundCOPD is characterized by persistent and progressive airway inflammation. Although neutrophilic airway inflammation is generally accepted to be a major factor in the pathogenesis of COPD, the influence of the agents used for the treatment of COPD on neutrophil functions such as chemotaxis is not fully understood.PurposeThe present study aimed to examine the influence of tiotropium bromide on the production of interleukin (IL)-8 from human airway epithelial cells and lung fibroblasts (LFs) after lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…However, the potential effects of antimuscarinics on structural and functional changes of bladders caused by BOO have not been explored so far. Nevertheless, recent findings implicate that muscarinic receptors are able to enhance the cell proliferation, modulate contractile protein expression and participate in the release of inflammatory cytokines [6-9]. But, up to date, the role of antimuscarinics and muscarinic receptors in bladder function and structure is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential effects of antimuscarinics on structural and functional changes of bladders caused by BOO have not been explored so far. Nevertheless, recent findings implicate that muscarinic receptors are able to enhance the cell proliferation, modulate contractile protein expression and participate in the release of inflammatory cytokines [6-9]. But, up to date, the role of antimuscarinics and muscarinic receptors in bladder function and structure is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tiotropium reduced inflammation and remodeling in several models of asthma ( Gosens et al, 2005 ; Bos et al, 2007 ; Ohta et al, 2010 ; Buels et al, 2012 ; Bosnjak et al, 2014 ). In addition, several in vitro studies also attest to the anti-inflammatory properties of tiotropium ( Buhling et al, 2007 ; Asano et al, 2008 ; Bateman, et al, 2009 ; Suzaki, et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In several animal models tiotropium has been found to attenuate acute and chronic pulmonary inflammation [ 30 32 ]. Several studies in vitro also showed that tiotropium could suppress LPS-induced the release of neutrophil chemotactic mediators by human airway epithelial cells, lung fibroblasts and alveolar macrophages [ 5 , 6 ]. Together with the finding showing inhibitory effect of tiotropium on Cd-induced inflammatory changes in the present model, including a significant decrease of neutrophils and protein concentration in BALF accompanied with a marked attenuation of extent and severity of acute pulmonary inflammatory infiltration, we suggest that the decrease of airway hyperresponsiveness might be related to the anti-inflammatory mechanisms of tiotropium.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of long-acting muscarinic antagonists (LAMAs) has been mentioned by several studies in vitro and in vivo [ 4 6 ]. Tiotropium has been reported to have an anti-inflammatory activity on cigarette smoke induced pulmonary inflammation in mice [ 4 ] and can inhibit cytokines production from structural and inflammatory cells [ 5 6 ]. However, whether tiotropium could reduce the severity and frequency of AECOPD by inhibiting neutrophilic infiltration remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%